Subacute edema progression after acute ischemic stroke: impact of intravenous alteplase administration and reperfusion degree - Olszewski, Wiktor; Cavalcante, Fabiano; van Poppel, Laura; Beenen, Ludo; Emmer, Bart J.; van den Wijngaard, Ido; Lemmens, Robin; Roos, Yvo; Marquering, Henk; Konduri, Praneeta; Majoie, Charles (Frontiers in Neurology, 2025)
IntroductionAlteplase is known to increase the risk of blood-brain barrier integrity disruption, potentiating hemorrhage and edema. Evolving edema reduces chances of good functional outcomes. There is a paucity of studies that investigate the role of alteplase administration in subacute edema progression. Here we aim to associate alteplase administration in combination with the degree of reperfusion on edema, measured by net water uptake.MethodsWe included 115 patients from the MRCLEAN NO-IV trial with baseline, 24-h and 1-week follow-up non-contrast CT scans. The cohort consisted of patients who received intravenous thrombolysis (IVT)+ endovascular treatment (EVT) vs. EVT alone. Net water uptake (NWU) was calculated as a ratio of mean lesion density compared to its homologous, contralateral region-of-interest. Unadjusted linear regression analysis was performed to assess the association between NWU progression and alteplase administration, successful reperfusion [expanded Thrombolysis in Cerebral Infarction (eTICI)2B/3], and excellent reperfusion (eTICI2C/3). Adjusted regression analysis was performed to correct for potential confounders.ResultsIVT administration was not statistically significantly associated with NWU progression. Regardless of treatment arm, there was substantial increase in NWU during the first 24 h and 1 week post-stroke. In adjusted analysis, successful reperfusion was significantly associated with reduced NWU progression at 24 h (β = −4.6; 95% CI: −8.4, −0.80) and 1 week (β = −6.5; 95% CI: −11, −2.3).ConclusionAlteplase administration prior to EVT did not impact the subacute edema progression in our cohort, whereas successful reperfusion was strongly associated with reduced edema progression, particularly at later timepoints. These results suggest that alteplase administration according to current guidelines is unlikely to contribute to accelerated edema progression and emphasize that achieving high-grade reperfusion is crucial for reducing secondary injury.